The Walloon settlers in Spiš in the Middle Ages - Miloš Marek (Folia Historica Cracoviensia, 2024)
In the kingdom of Hungary we assume the presence of a Romance-speaking population as early as in the 11th century. Other groups of Latins, mainly Walloons, immigrated during the 12th century to Transylvania, along with the Flemish people, and to other important cities of the kingdom (Esztergom, Székesfehérvár, Oradea Mare, Pécs, Zagreb). But also into Spiš county. The most important Wallonian locality in the upper part of the country (Slovakia) was established in Spišské Vlachy located in the vicinity of the important German locality of Spišské Podhradie, where Saxon ʻguestsʼ were the first to be documented in Spiš. The presence of Walloons in Spiš is generally associated with the construction of the nearby Spiš castle although there may have been other reasons for their arrival. The local settlement is first recorded in sources in 1243, when King Bela IV. granted the settlers from Spišské Vlachy a special privilege. But Latin hospites in Spiš county lived not only in Spišské Vlachy and its immediate surroundings. The presence of individuals from the Romance language area is testified in other localities of Spiš as well, mostly in villages of the Hornád river valley (Aranyás, Mečedelovce, Odorín, Žehra and so on). The Wallonian community in Spiš wasn´t very numerous in comparison with local Slavs or German (Saxon) settlers and very soon was gradually assimilated in the domestic Slovak or German environment.